Hormonal regulation of an islet-specific enhancer in the pancreatic homeobox gene STF-1. - Sharma, S (1997)
The homeobox protein STF-1 appears to function as a master control switch for expression of the pancreatic program during development. Here we characterize a composite enhancer which directs STF-1 expression to pancreatic islet cells via two functional elements that recognize the nuclear factors HNF-3beta and BETA-2. In keeping with their inhibitory effects on islet cell maturation, glucocorticoids were found to repress STF-1 gene expression by interfering with HNF-3beta activity on the islet-specific enhancer. Overexpression of HNF-3beta suppressed glucocorticoid receptor-mediated inhibition of the STF-1 gene, and our results suggest that the expansion of pancreatic islet precursor cells during development may be restricted by hormonal cues which regulate STF-1 gene expression.